Design and development of Palmyra fruit pulp production equipment through sustainable approach. (2022) - Subharaj, C.; Logesh, K.; Joe Patrick Gnanaraj, S.; Appadurai, M.; Maria Antony Sebastin Vimalan, P.
Abstract: The goal of the article is to suggest the creation of an environmentally friendly product to take the place of the traditional Palmyra tree fruit pulp while still satisfying anticipated demands and having a focus on economic viability and sustainability. The Palmyra palm fruit and to create a dependable pectin extraction process by using creative design and development of modern equipment. To present a green design, analysis and manufacturing for creating model of fruit processing unit in Palmyra tree. Palmyra fruit is a natural and nutritionally rich fruit that may be used to make a variety of value-added goods. Palmyra pulp, collected from ripe fruit, is utilized in a variety of traditional foods, and its juice is a seasonal, low-cost drinking juice due to lack of mechanization. It is used to treat nausea, vomiting, worm infestations, and as an expectorant and liver tonic. A little layer of sugar palm fruit jelly applied to the affected area has a calming effect and relieves the itching caused by prickly heat right away. Adopting a sustainable system entails eco-design and development across the board. This paper's outcome would create a manufacturing process unit that would use modern concepts in an organization with a startup industry level, as well as help consumers by providing a hygienic product.